KEPENTINGAN INDONESIA DAN JEPANG DALAM IMPLEMENTASI SKEMA GOVERNMENT TO GOVERNMENT (G TO G) INDONESIAN-JAPAN ECONOMIC PARTNERSHIP AGREEMENT (IJEPA) - Putri, Finka Fadhilah; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This research analyzes the motivations of Indonesia and Japan in implementing the Government-to-Government (G to G) scheme within the framework of the Indonesian-Japan Economic Partnership Agreement (IJEPA). With the ratification of the Memorandum of Understanding (MoU) between JICWELS and BP2MI, the G to G scheme serves as a mechanism for Indonesia and Japan to facilitate the deployment of Indonesian migrant workers (PMI) to Japan, specifically for careworker and nurse positions. This study examines the underlying interests of both countries in implementing the G to G IJEPA scheme. This research employs a qualitative descriptive analysis method. To examine Indonesia and Japan’s motivations, the study applies the bilateral labor cooperation theory. Data collection was conducted using primary sources through interviews with KP2MI/BP2MI, BP3MI Riau and secondary sources from academic journals, official websites of MOFA Japan, KP2MI/BP2MI, and other relevant institutions. The findings indicate that Indonesia is driven by interests to reduce unemployment, optimize the utilization of underemployed nursing personnel to enhance the quality of its human resources. Meanwhile, Japan aims to address labor shortages, particularly in the caregiving sector, as a result of demographic challenges and a growing elderly population. The G to G scheme serves as a strategic mechanism for both countries to fulfill their respective needs. Keywords: IJEPA, G to G Scheme, Indonesian Migrant Workers, Bilateral Cooperation.